Fine tuning of size and morphology of magnetite nanoparticles synthesized by microemulsion - Singh P.; Upadhyay C. (My University, 2025)
The synthesis parameters crucially affect the physical and chemical parameters of nanoparticles. Magnetite (Fe3O4) nanoparticles were synthesized using microemulsion method. This method does not require high temperature synthesis, nitrogen environment and/or pH regulation during synthesis process. We are presenting here a systematic study on role of different associated parameters of microemulsion synthesis method on the formation of Fe3O4 nanoparticles. From X-ray Diffraction and Transmission Electron Micoscopy data analysis the size of synthesized particles were observed to be <10 nm. The critical concentration of ferrous-ferric solution to obtain particles in single phase has been found to be ≤0.09 M and ≤0.184 M, respectively. The variation of molar concentration (0.01 M ≤x≤ 0.1 M) of CTAB leads to formation of Fe3O4 nano-scale particles of distinct morphologies e.g. nano-cubes, pentagons and spheres. The number of ferrous and ferric ions involved in the formation decides the size of the nanoparticles. The single crystallographic phase is obtained in reaction temperature range of 65°C<T< 72°C. The method facilitates to produce nanostructures having narrower size distribution along with good reproducibility. © 2018 Author(s).